1996
DOI: 10.1088/0964-1726/5/6/012
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of an adaptive sandwich beam

Abstract: A new adaptive sandwich structure is constructed using the shear mode of piezoelectric materials. Governing equations for the proposed beam and its surface-mounted counterpart are derived based on the variational principle. Static solutions of a cantilever sandwich beam and its corresponding surface-mounted beam are obtained based on the derived general formulations. The theoretical formulations are verified by finite element analysis. Furthermore, stress distributions of the two types of adaptive beams are al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
148
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(163 citation statements)
references
References 5 publications
3
148
0
Order By: Relevance
“…Validation. In order to validate the new FE formulation and the computer program developed, cantilever plane strain beams (a) and (b) made of aluminum substrate with surface-bonded and embedded PZT-5H layers, respectively, are considered, which have been analyzed in [Zhang and Sun 1996;Benjeddou et al 1999]. The configurations and the dimensions of the beams are shown in Figure 5 and the material properties are selected as in the references mentioned above:…”
Section: Finite Element Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Validation. In order to validate the new FE formulation and the computer program developed, cantilever plane strain beams (a) and (b) made of aluminum substrate with surface-bonded and embedded PZT-5H layers, respectively, are considered, which have been analyzed in [Zhang and Sun 1996;Benjeddou et al 1999]. The configurations and the dimensions of the beams are shown in Figure 5 and the material properties are selected as in the references mentioned above:…”
Section: Finite Element Modelmentioning
confidence: 99%
“…The shear mode piezoelectric layer in beam (a) is divided into two sublayers and those in beam (b) are modeled as one sublayer for the discretization of potential φ. The present results for the deflection profile of the centerline (z = 0) are compared in Figure 6 with the FE FSDT results of Benjeddou et al [1999] for beam (a) and with the analytical FSDT solution of Zhang and Sun [1996] for beam (b). It is found that the present results are in excellent agreement with the reference results in both cases.…”
Section: Finite Element Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…those of Zhang and Sun [54,55], Benjeddou et al [56]. Some results are given varying the actuator position along the x-axis, the deflection at the free edge is investigated for each position of the piezoelectric patch, see Figure 15, and compared with the literature solutions [54,56], here named Sun & Zhang, and Benjeddou et al, respectively.…”
Section: Sandwich Cantilever Plate Shear-actuated In Mode-15mentioning
confidence: 99%
“…However, all these models based on classical theory neglect transverse shear and hence are inadequate for shorter and thick beams (Benjeddou et al, 1999). Zhang and Sun (1996) proposed a classical Sandwich Beam Theory (SBT) based analytical solution in which the thick core is modeled as Timoshenko beam and the relatively thin faces as Euler-Bernoulli beam. Based on SBT, Raja et al (2002) proposed beam finite element to study the behaviour of piezoelectric smart beams.…”
Section: Introductionmentioning
confidence: 99%